Noninvasive Method for a Statewide Survey of Eastern Hellbenders Cryptobranchus alleganiensis Using Environmental DNA - Amy J. Santas; Tyler Persaud; Barbara A. Wolfe; Jenise M. Bauman (International Journal of Zoology)
Traditional survey methods of aquatic organisms may be difficult, lengthy, and destructive to the habitat. Some methods are invasive and can be harmful to the target species. The use of environmental DNA (eDNA) has proven to be effective at detecting low population density aquatic macroorganisms. This study refined the technique to support statewide surveys. Hellbender presence was identified by using hellbender specific primers (cytochrome b gene) to detect eDNA in water samples collected at rivers, streams and creeks in Ohio and Kentucky with historical accounts of the imperiled eastern hellbender (Cryptobranchus a. alleganiensis). Two sampling protocols are described; both significantly reduced the amount of water required for collection from the previously described 6 L collection. Two-liter samples were adequate to detect hellbender presence in natural waterways where hellbenders have been previously surveyed in both Ohio and Kentucky—1 L samples were not reliable. DNA extracted from 3 L of water collected onto multiple filters (1 L/filter) could be combined and concentrated through ethanol precipitation, supporting amplification of hellbender DNA and dramatically reducing the filtration time. This method improves the efficiency and welfare implications of sampling methods for reclusive aquatic species of low population density for statewide surveys that involve collecting from multiple watersheds.